Minority of Male Teachers in Kindergartens as a Result of Gender Stereotypes in Society - Nur Rohmah; Fahri Hidayat (Universitas Muhammadiyah Enrekang, 2023)
The phenomenon of the minimum number of male kindergarten teachers is increasingly visible in Indonesia, so that people increasingly think that kindergarten teachers are a woman's profession. This results in an imbalance of gender roles in Kindergarten. Discussion of gender-related issues in kindergarten is considered too commonplace and often escapes society's attention. The aim of this research is to describe and analyze gender stereotypes which result in a minority of male teachers in kindergarten. Not only that, this research also provides an alternative view of the role of a man as a teacher in kindergarten. This research is a literature study that uses a qualitative approach. The results of this research are stereotypes that grow and develop in society regarding male kindergarten teachers, including; firstly, kindergarten teachers are attached to feminine traits, while men are attached to masculine traits, secondly, the assumption is that male kindergarten teachers are